Coasts, Marine Structures and Breakwaters Adapting to Change: Proceedings of the 9th International Conference Organised by the Institution of Civil Engineers and Held in Edinburgh on 16 to 18 September 2009 - Allsop, William (Thomas Telford Limited, 2010)
The 2 volume proceedings of the 9th ICE Conference on Coastal Structures and Breakwaters discusses the state of the art in analysis, design and construction of breakwaters and other types of coastal structures, including interaction between coastlines and structures, and vice versa.
Keywords: elektronické knihy; electronic books